Thank You's (Symphony in the Flint Hills, 2009)
Acknowledgements and thanks for all those involved in the Symphony in the Flint Hills and the production of the Field Journal.
Keywords: music; horizon; sponsors; patrons; volunteers; thanks; board; editor; director; Home on the Range; people; media support; Thanks